Unilateral intramuscular needling can improve ankle dorsiflexor strength and muscle activation in both legs - Li-Ping Huang; Shi Zhou; Ming Ao; Mei-Ling Zhao; Li-Qin Zhang; Long-Jun Cao (Elsevier, 2015)
Background/Objective: The aim of this study was to determine whether unilateral manual needling at nonacupoints could result in bilateral strength gain similar to that found in electroacupuncture at specific acupoints. Methods: Fifty healthy male volunteers with an age range of 19-27 years were recruited and randomly allocated into five groups: (1) manual acupuncture and (2) electroacupuncture at two acupoints (ST-36 and ST-39); (3) manual acupuncture and (4) electroacupuncture at two nonacupoints on the tibialis anterior muscle; and (5) control group. The intervention groups received needling in each session on the right leg for 15 minutes in Week 1, 20 minutes in Week 2, and 30 minutes in Weeks 3-8, three sessions per week. The maximal isometric ankle dorsiflexion strength and muscle activation (as determined by twitch interpolation) of both legs were assessed pre, post, 2 weeks post, and 3 weeks post the experimental period. Results: Mixed models (linear) with repeated-measures analysis identified significant strength gains (p < 0.01) after the intervention period in both limbs, while no significant differences were detected between the intervention groups and between the two legs, and no change was found in the control group. A significant improvement in muscle activation (p < 0.01) was also observed in both legs in the intervention groups. Conclusion: It was concluded that both unilateral manual and electric needling caused significant bilateral strength gain, and this effect was not specific to the selected acupoints or electric stimulation. The strength gain was sustained for at least 3 weeks after the 8-week intervention.